THE PENOMENON OF APARTHEID TOWARD AFRICAN PEOPLE IN “ESCAPE FROM PRETORIA”: HISTORICAL APPROACH - Pijar Omar Piscesco; Tomi Arianto (Asosiasi dosen IDEBAHASA KEPRI, 2021)
The purpose of this research is to reveal how the phenomenon of breaking the practice of apartheid construction toward the black race in the escape from Pretoria movie. The construction of apartheid has placed the black race under the domination of the white race and this behavior is legitimate in the everyday life of society. The dichotomy that places the black race as an inferior race has become a normal habit in society. By using a historical approach, the researchers revealed how the apartheid construction was exposed through the black racial figures in the movie. Qualitative descriptions with historical approach analysis techniques were used as the method in this study. The results of this study reveal: the first, the apartheid construction phenomenon that occurred in the movie. The second is the efforts by breaking the apartheid construction from in movie. The phenomena found related to the construction of apartheid in the movie include: 1) the paradigm of society that perceives whites to be better than blacks, 2) racism. Breaking the habits is revealed through the character Tim Jenkin by changing the paradigm of thinking of the white race after escaping from a Pretoria prison.